PENGEMBANGAN LITERASI SAINS DAN IDENTITAS BUDAYA SISWA MELALUI PENDEKATAN ETNO-PEDAGOGI DALAM PEMBELAJARAN SAINS - Yuli Rahmawati; Achmad Ridwan; Sylvia Faustine; Sitti Syarah; Ibrahim Ibrahim; Pramita Cucu Mawarni (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2020)
SCIENCE LITERACY AND STUDENT CULTURAL IDENTITY DEVELOPMENT THROUGH ETHNO-PEDAGOGY APPROACH IN SCIENCE LEARNING AbstractThis study aims to develop and apply ethno-pedagogy learning models in science learning to develop scientific literacy and students' cultural identity in the solar system topic. The study was conducted at SMPN 4 Bolo in the even semester of the 2018/2019 school year with 26 research subjects consisting of grade seven students. The study was conducted using qualitative analysis methods by collecting data through observation, reflective journals, student interviews, and scientific literacy tests. The ethno-pedagogy model is carried out through five stages of learning: self-identification, Content Integration, Collaboration, Dialogue, and Reflection. The results showed that the Etnopedagogy learning model impacted the development of students' scientific literacy and student's cultural identity. Based on the students' scientific literacy test as a whole showed that as many as 6.25% of students reached excellent levels and 31.25% of students reached good levels, 50% of students reached sufficient levels, 12.50% of students reached unfavorable levels, and there were none of the students who are at a not very good level. Science learning with the Ethno Pedagogy model provides opportunities for students to develop scientific literacy and learn to understand their cultural identity, foster a sense of love and pride for Indonesia, and responsibility to preserve its culture. AbstrakPenelitian ini bertujuan untuk mengembangkan dan menerapkan model pembelajaran etnopedagogi dalam pembelajaran IPA untuk mengembangkan literasi sains dan identitas budaya siswa pada materi sistem tata surya. Penelitian dilaksanakan di SMPN 4 Bolo pada semester genap tahun ajaran 2018/2019 dengan subyek penelitian terdiri dari 26 orang siswa kelas VII. Penelitian dilakukan dengan menggunakan metode analisis kualitatif dengan mengumpulkan data melalui observasi, reflektif jurnal, wawancara siswa, dan tes literasi sains. Model etnopedagogi dilakukan melalui lima tahapan pembelajaran, yaitu self-identification, Content Integration, Collaboration, Dialogue, dan Reflection. Hasil penelitian menunjukkan bahwa model pembelajaran Etnopedagogi memiliki dampak dalam pengembangan literasi sains siswa dan identitas budaya siswa. Berdasarkan tes literasi sains siswa secara keseluruhan menunjukkan sebanyak dapat diketahui bahwa sebanyak 6,25% siswa mencapai level baik sekali dan 31,25% siswa mencapai level baik, 50% siswa mencapai level cukup, 12,50% siswa mencapai level kurang baik, dan tidak ada lagi siswa yang berada pada level kurang baik sekali. Pembelajaran sains dengan model Etnopdagogi memberikan kesempatan kepada siswa untuk mengembangkan literasi sains dan belajar untuk memahami identitas budayanya, menumbuhkan rasa cinta tanah air, bangga dan tanggung jawab untuk melestarikan budayanya.